A Metaphor Analysis of the Issues Palestine Genocide in Online News Texts - Suherman, Kafka Nabawi (Indonesian Journal of Applied Linguistics Review, 2024)
This study looks into what kinds of metaphors are utilized in Al Jazeera headlines about Palestine. Using qualitative research methods, 16 headlines were examined using Lakoff and Johnson's conceptual metaphor theory, which divides metaphors into structural, orientational, and ontological categories. The study found that orientational metaphors are the most common (50%), followed by ontological (31.25%) and structural metaphors (18.75%). The prevalence of orientational metaphors emphasizes Al Jazeera's use of spatial and relational language to frame the Palestinian struggle and complex global concerns.